2013
DOI: 10.1007/s00345-013-1102-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes and patient satisfaction rates among elderly male aged ≥75 years with inflatable penile prosthesis implant for medically refractory erectile dysfunction

Abstract: Men aged ≥75 years reported satisfactory outcome with IPP surgery with no statistical significant difference identified across device survival and satisfaction rates compared to men aged <75 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 17 publications
1
13
1
Order By: Relevance
“…With aging, there is a recognized functional decline in both innate and adaptive immune response [29], predisposing elderly patients to infection. The one prior study on post-IPP infections among the elderly found no infections among the 30 patients aged ≥75 [30]. Our study reinforces this data, showing no infections in our 31 patients aged ≥75.…”
Section: Discussionsupporting
confidence: 91%
“…With aging, there is a recognized functional decline in both innate and adaptive immune response [29], predisposing elderly patients to infection. The one prior study on post-IPP infections among the elderly found no infections among the 30 patients aged ≥75 [30]. Our study reinforces this data, showing no infections in our 31 patients aged ≥75.…”
Section: Discussionsupporting
confidence: 91%
“…Infected or eroding prostheses must be surgically removed (Alberson et al, 2012). Chung, Solomon, DeYoung, and Brock (2013) assessed clinical outcomes and patient satisfaction rates among men post inflatable penile prosthesis (IPP) implantation. A retrospective chart review of all men who received initial IPP implantation between 2006 to 2010 indicated that the majority of men were satisfied and would recommend IPP to other men with ED.…”
Section: Surgical Therapymentioning
confidence: 99%
“…The inflatable penile prosthesis (IPP) has become the standard of care for severe erectile dysfunction refractory to non-surgical therapies. IPP placement is a reliable, safe surgical treatment option with high patient satisfaction rates [1][2][3]. The use of Rear Tip Extenders (RTEs) is an underexplored aspect of IPP placement.…”
Section: Introductionmentioning
confidence: 99%